IMPROVING VOCABULARY OF THE STUDENTS BY USING ANIMATION VIDEO - Yumin Fatin; Ahmad Talib; La Sunra (Universitas Negeri Makassar, 2022)
This research aimed to find out whether or not the animation video improved students’ vocabulary. This study's population consisted of second-grade students from senior high school 4 Sidenreng Rappang in the 2021/2022 academic year. The sample was composed of 21 students and was drawn using the cluster random sampling approach. The findings of this study suggested that the utilization of animation video improved pupils' vocabularies. The value of the t-test (21,864) was larger than the value of the t-table (2,086) with the level of significance (p) = 0, 05 and the degree of freedom (df) 20. The students' pretest means score was (39,62), while their post-test mean score was (39,62). (80,38). It can be concluded that using animation video can significantly improve the vocabulary of the second-grade students of senior high school 4 Sidenreng Rappang.